Conflicto y reciprocidad en los pueblos andinos. El caso de Angaraes - Plasencia Soto, Rommel (Revista Española de Antropología Americana, 2001)
In this paper I try to show the construction of colaborate social and territorial alliances from two important principles that organized the andean society and mind, hicrarchy and reciprocity. That structure allowed to organize the abundant labour force of Andean people. In this way, an effective agricultural civilization was organized, that was unique in Indian America. Five rural communities of Central Peru are taken as an example.